Thelazia callipaeda in wild carnivores from Romania: new host and geographical records - Mihalca, Andrei Daniel; Ionică, Angela Monica; D'Amico, Gianluca; Daskalaki, Aikaterini Alexandra; Deak, Georgiana; Matei, Ioana Adriana; Șimonca, Vasile; Iordache, Daniel; Modrý, David; Gherman, Călin Mircea (Parasites & vectors, 2016)
BACKGROUND: Thelazia callipaeda is a vector-borne zoonotic nematode parasitizing the conjunctival sac of domestic and wild carnivores, rabbits and humans, with a vast distribution in Asia and the former Soviet Union. In Europe, the nematode has an emerging trend, being reported in Italy, France, Switzerland, Germany, Spain, Portugal, Bosnia and Herzegovina, Croatia, Romania, Greece and Serbia, with human cases known in Italy, France, Spain, Serbia and Croatia. In Romania, the infection was so far reported only in dogs, whereas there are no reports in wildlife despite the large numbers of wild carnivores in the country. The aim of this study was to evaluate the role of wild carnivores in the natural cycle of T. callipaeda in Romania. METHODS: Between 2014 and 2016, 89 wild carnivores (64 golden jackals, Canis aureus, 13 grey wolves, Canis lupus, nine wildcats, Felis silvestris and three Eurasian lynxes, Lynx lynx) have been examined. During the necropsy, both eyes of all the examined animals have been thoroughly inspected for the presence of parasites. If present, all nematodes were collected in absolute ethanol (for molecular analysis of the partial cox1 gene) or in 4 % formalin (for morphological identification). RESULTS: In total, three animals were found to be infected with T. callipaeda: a grey wolf, a golden jackal and a wildcat. The BLAST analysis of all the sequences showed a 100 % similarity to T. callipaeda haplotype h1. To the best of our knowledge, this study represents the first report of T. callipaeda in golden jackals, and the first study on T. callipaeda in wildlife from Romania. CONCLUSION: Our data broaden the host spectrum and geographical distribution of T. callipaeda, highlighting the role of wild carnivores as natural reservoirs for the infection and confirming the ongoing expanding trend of this zoonotic nematode in Europe.
Keywords: Thelazioidea; Canis aureus; Thelazia callipaeda; Canis lupus; Carnivora; infekce hlísticemi řádu Spirurida; Animals; Romania; Felis silvestris; zvířata; Spirurida Infections; Rumunsko